Pengaruh Commmunity of Inquiry terhadap Student’s Satisfaction in Online Learning di Universitas Islam Bandung - Puri Luthfiarini; Susandari (UNISBA Press, 2022)
Abstract. E-learning implementation during Pandemic covid-19, students experienced dissatisfaction towards the significance of learning attendance, social relationship, and comprehension. This phenomenon indicates problems with the perception of Community of Inquiry which consists of Teaching Presence, Social Presence, and Cognitive Presence that has effects on student's online learning unsatisfactory. This study aims to find out the Impact of Community of Inquiry toward Student's Satisfaction Online Learning in Universitas Islam Bandung. The instruments used are Community of Inquiry from Shea & Bidjerano (2010), and Students Satisfaction Online Learning from Dziuban (2015). The sampling used in this study is Cluster random sampling, taking 377 students from Social study fields. This study used multiple linier regression method. Results shows that Community of Inquiry has a significant impact on Students Satisfaction Online Learning up to 44.3% with 0.003 signification score. The majority of students (56.23%) perceives Teaching Presence as